The polyamines and endophytes of gousiekte-causing and non-pathogenic Vangueria and Pavetta species - Meyer, J.J.M. (Jacobus Johannes Marion) (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2014.